2018
DOI: 10.3389/fpubh.2018.00298
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Markers of Phthalate Exposure in Plasma and Urine of Pregnant Women

Abstract: Phthalates are known endocrine disruptors and found in almost all people with several associated adverse health outcomes reported in humans and animal models. Limited data are available on the relationship between exposure to endocrine disrupting chemicals and the human metabolome. We examined the relationship of metabolomic profiles in plasma and urine of 115 pregnant women with eleven urine phthalate metabolites measured at 26 weeks of gestation to identify potential biomarkers and relevant pathways. Targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 78 publications
1
39
0
Order By: Relevance
“…We observed numerous associations of metabolomic markers involved in lipid and nucleic acid metabolism and the inflammatory response with both urinary phthalate metabolites and maternal BMI. This study aims to determine the association between maternal metabolomic profiles in pregnancy and child DNA methylation at birth, emphasizing metabolites enriched for lipid pathways that were confirmed as relevant in previous work in CHAMACOS [18]. This study will contribute to the growing body of evidence of the influence of the early life environment on epigenetic mechanisms.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…We observed numerous associations of metabolomic markers involved in lipid and nucleic acid metabolism and the inflammatory response with both urinary phthalate metabolites and maternal BMI. This study aims to determine the association between maternal metabolomic profiles in pregnancy and child DNA methylation at birth, emphasizing metabolites enriched for lipid pathways that were confirmed as relevant in previous work in CHAMACOS [18]. This study will contribute to the growing body of evidence of the influence of the early life environment on epigenetic mechanisms.…”
Section: Introductionmentioning
confidence: 76%
“…In this study, we focused on maternal metabolites previously identified to be relevant to lipid biosynthesis, arachidonate enrichment and release, and inflammatory signaling [18]. The 92 plasma metabolites in the study included fatty acids, lysolipids, phospholipids, sphingolipids, monoacylglycerols, diacylglycerols, and triacylglycerols (Table 2, Figs 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations